Aturan Hukum Lembaga Keuangan Mikro Syariah (Bmt Dan Koperasi Syariah) Beserta Akad Akadnya - ridwan, mohammad ridwan (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2022)
Law No. 1 of 2013 concerning Microfinance Institutions was born, LKMS in Indonesia are known as Baitul Mal wa Tamwil (BMT) or Sharia Savings and Loans and Financing Cooperatives (KSPPS) which are generally incorporated as cooperatives. Based on sharia principles, cooperatives are legally incorporated under the supervision of the ministry of cooperatives and small and medium enterprises. The existence of this dualism of legal regulations has led to overlapping regulations, supervision and guidance by related agencies, as well as contradictions in the regulations between one another. This legal problem requires a solution through the reformulation of legal regulations relating to Islamic MFIs. Microfinance institutions (MFIs) in Indonesia are currently growing rapidly and have an important role in improving the people's economy. The rapid development of this MFI is because almost 51.2 million units or 99.9% of business actors in the Indonesian economy are dominated by micro and small business units (Ali sakti: 2013). MFIs can be said to be one of the important pillars in the financial intermediation process needed by small and medium-sized communities for consumption and production as well as storing their business results. In Indonesia, MFIs are regulated in Law no. 1 of 2013 concerning Microfinance Institutions. According to Article 1 (1) of Law no. 1 of 2013 concerning Microfinance Institutions, what is meant by MFIs are: financial institutions specifically established to provide business development services and community empowerment, either through loans or financing in micro-scale businesses to members and the public, managing deposits, as well as providing development consulting services business that is not solely for profit. Based on the definition above, it can be understood that an MFI is a financial institution that functions as an intermediary institution that aims not only to seek profit (profit motive), but also has other goals, namely social motives whose activities are more in the nature of community development.